2019
DOI: 10.1186/s40729-019-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-drill guided vs. full-guided implant insertion in artificial mandibles—a prospective laboratory study in fifth-year dental students

Abstract: Background As a growing field in dentistry, the practical education during the undergraduate curriculum in implant dentistry should be extended. Not only the theoretical background but also practical skills are crucial to place implants in patients. In order to determine the exact implant position, several positioning aids are available. In the present laboratory study, the accuracy of implant insertion using two different guiding modes in a group of inexperienced participants was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
1
31
1
1
Order By: Relevance
“…In addition, this superiority was shown for anterior and posterior implants. Such observations confirm the advantage of the FG protocol in controlling all the steps of osteotomy and implant placement [7,9,15,16]. On the contrary, the inaccuracies of the PG and FH protocols were generally similar and tended to be approximately double the inaccuracies of the FG protocol.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In addition, this superiority was shown for anterior and posterior implants. Such observations confirm the advantage of the FG protocol in controlling all the steps of osteotomy and implant placement [7,9,15,16]. On the contrary, the inaccuracies of the PG and FH protocols were generally similar and tended to be approximately double the inaccuracies of the FG protocol.…”
Section: Discussionsupporting
confidence: 70%
“…For example, Rungcharassaeng et al found that the FG protocol reduced differences between experienced and inexperienced operators for placing single posterior implants no difference between experienced and inexperienced operators when FG protocol guides were used, while the differences became obvious when implants were placed without surgical guides [13,14]. According to Schulz et al, in the hand of final-year dental students, FG implant placement was more accurate than PG implant placement [15]. The superior accuracy and the less variation of the FG protocol is most likely related to the control of all the drilling steps and the implant placement via sequential use of precision sleeves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A correct combination of anatomical information and virtual prosthetic planning allows the positioning of the implant according to the prosthetic's needs [10]. The incorporation of the digital mock-up into the dental implant planning process and digital flow in implantology can influence the accuracy of dental implant placements and reduce the variability associated with the professional experience [11].…”
Section: Introductionmentioning
confidence: 99%